2023
DOI: 10.21203/rs.3.rs-2605378/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ankrd11, a chromatin regulator and a KBG syndrome risk gene, is a critical regulator of cardiac neural crest cell biology and heart development

Abstract: ANKRD11 (Ankyrin Repeat Domain 11) is a chromatin regulator and a risk gene for KBG syndrome, a rare developmental disorder characterized by multiple organ abnormalities, including cardiac defects. However, the role of ANKRD11 in heart development is unknown. The neural crest plays a leading role in embryonic heart development, and its dysfunction is implicated in many congenital heart defects. Here, we demonstrate that conditional knockout of Ankrd11 in the murine embryonic neural crest leads to a severe cong… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…1A) (Watson et al 2021;Li et al 2022;Imayoshi et al 2006). Upon TMX administration, Cre causes recombination at the floxed exon 7 of Ankrd11 in NPCs, creating a frameshift mutation that encompasses all known functional domains of the protein (Roth et al 2021;Kibalnyk et al 2023). We confirmed the loss of Ankrd11 mRNA via qRT-PCR from cultured primary neurospheres, which were generated from cells micro dissected from E15.5 Ankrd11 nscKO and Ankrd11 Contol neocortices 24 hours after TMX injection.…”
Section: Loss Of Ankrd11 In Npcs Results In Aberrant Postnatal Ob Dev...supporting
confidence: 53%
See 2 more Smart Citations
“…1A) (Watson et al 2021;Li et al 2022;Imayoshi et al 2006). Upon TMX administration, Cre causes recombination at the floxed exon 7 of Ankrd11 in NPCs, creating a frameshift mutation that encompasses all known functional domains of the protein (Roth et al 2021;Kibalnyk et al 2023). We confirmed the loss of Ankrd11 mRNA via qRT-PCR from cultured primary neurospheres, which were generated from cells micro dissected from E15.5 Ankrd11 nscKO and Ankrd11 Contol neocortices 24 hours after TMX injection.…”
Section: Loss Of Ankrd11 In Npcs Results In Aberrant Postnatal Ob Dev...supporting
confidence: 53%
“…We and others have previously shown aberrant neuronal positioning in the cortex of mice that carry a splice mutation in the Ankrd11 gene (Yoda mice) or in mice with Ankrd11 knockdown in murine embryonic cortical NPCs, which could suggest aberrant neuronal migration (Gallagher et al 2015;Ka and Kim 2018). We have also shown that loss of Ankrd11 in the embryonic neural crest results in modest impairment of cardiac neural crest cell migration in the developing heart outflow tract (Kibalnyk et al 2023). Our report is the first to show severe migration defects via the abrogated postnatal RMS in the NPC-specific Ankrd11 knockout mice.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…1A) [61][62][63]. Upon TMX administration, Cre causes recombination at the floxed exon 7 of Ankrd11 in NPCs, creating a frameshift mutation that encompasses all known functional domains of the protein [58,59]. The progeny from this TMX-injected cross that contain NestinCre ERT2 will be referred to as Ankrd11 nscKO , and litter mates that do not contain a NestinCre ERT2 will be referred to as Ankrd11 Contol (Fig.…”
Section: Loss Of Ankrd11 In Npcs Results In Aberrant Postnatal Ob Dev...mentioning
confidence: 99%
“…Ankrd11 fl/fl mice in which exon 7 of the Ankrd11 gene is flanked by LoxP sites are described in [58,59]. RosaYFP STOP/STOP (B6.129X1-Gt(ROSA)26Sortm1(EYFP) Cos/J, stock # 006148) mice were obtained from Jackson Laboratories [60].…”
Section: Animalsmentioning
confidence: 99%